Iron and Stony-Iron Meteorites - Benedix, Gretchen; Haack, H.; McCoy, T. (Elsevier Science BV, 2013)
Without iron and stony-iron meteorites, our chances of ever sampling the deep interior of a differentiated planetary object would be next to nil. Although we live on a planet with a very substantial core, we will never be able to sample it. Fortunately, asteroid collisions provide us with a rich sampling of the deep interiors of differentiated asteroids.Iron and stony-iron meteorites are fragments of a large number of asteroids that underwent significant geological processing in the early solar system. Parent bodies of iron and some stony-iron meteorites completed a geological evolution similar to that continuing on Earth – although on much smaller length- and timescales – with melting of the metal and silicates; differentiation into core, mantle, and crust; and probably extensive volcanism. Iron and stony-iron meteorites are our only available analogues to materials found in the deep interiors of Earth and other terrestrial planets. This chapter deals with our current knowledge of these meteorites. How did they form? What can they tell us about the early evolution of the solar system and its solid bodies? How closely do they resemble the materials from planetary interiors? What do and do not we know?